Produção concomitante de lipases e biossurfactantes em fermentação em estado sólido para uso em biorremediação - Kreling, Naiara Elisa (2021)
Biosurfactants and lipases are biocompounds that can be obtained through solid-state fermentation (FES) with the potential for environmental application, as in the use in bioremediation of oily contaminants in soils, such as biodiesel, which although is less harmful to the environment than diesel, can cause contamination of soil and water. Among the microorganisms used in FES, fungi are the most recurrent, with a data gap to the use of bacteria in FES. The aim was to simultaneously produce lipases and biosurfactants via FES from the filamentous fungus Aspergillus niger and the bacterium Bacillus methylotroficus and to evaluate the use of the fermented medium in the bioremediation of soil contaminated with 20% biodiesel. Studies were also carried out on the influence of the addition of biocompounds on the adsorption of the contaminant to the soil. Different agro-industrial residues were evaluated for the composition of the culture medium (sugar cane molasses, wheat bran, corn cob, soybean meal and soybean waste), and different nitrogen, moisture, and inducers percentages were evaluated. The optimization of biocompound production conditions for the Aspergillus niger fungus occurred with the use of 80% wheat bran, 20% corn cob, 0.5% sugarcane molasses, 60% nitrogen, and 5% of inducer (10.74 ± 0.54 Units of lipolytic activity and 6.67 ± 0.06 Emulsification Units). Over 90 days of bioremediation assay, the greatest biodegradation (74.40±1.76%) was verified when using the application of fermenting bran containing the produced biocompounds. For the bacterium Bacillus methylotrophicus, the culture medium composed of 80% wheat bran and 20% corn cob, 1% sugar cane molasses, 2% nitrogen source, 75% moisture, and 1% inducer presented the better concomitant production of biosurfactants and lipases (24.61% Surface Tension Reduction and 43.54 ± 1.20 Units of lipolytic activity in soil, respectively). In the bioremediation assay evaluated over 90 days, the greatest biodegradation of the contaminant was observed in 60 d of the experiment (72.08 ± 0.36%), when the fermenting bran containing the produced biocompounds was applied. The aim of simultaneous production of biocompounds via FES was achieved for both the filamentous fungus and the bacteria and it was concluded that the FES processes have the potential to contribute to the acceleration of the bioremediation processes of oily residues in soils, and may reduce the costs related to the use of biosurfactants and purified lipases.